The Influence of Principal Leadership on Entrepreneurial Teacher Performance through Job Satisfaction and Teacher Compensation - Wilujeng, Sri; Wardana, Ludi Wishnu; Sumanto, Agus (International Journal of Business, Law, and Education, 2023)
As times progress, people are required to always improve their quality and abilities to be able to compete in this fairly tight competition. Research conducted by researchers on education has highlighted the quality of teaching as an important factor in school learning outcomes and student output. The aim of this research is to determine the influence of principal leadership on teacher performance which is mediated by job satisfaction and teacher compensation. This research uses a quantitative descriptive approach with explanatory research. The sample used in this research was vocational school entrepreneurship teachers throughout the district. Mojokerto with sample 94 entrepreneurship teachers as respondents. The results of this research are that the principal's leadership has no influence on teacher performance, but it becomes significant if the principal's leadership affects teacher performance through job satisfaction